Preoccupation with Death Wish in Samuel Beckett’s Plays Waiting for Godot and Endgame : A Psychobiography - Muhammad Adek (Vivid: Journal of Language and Literature, 2014)
Waiting for Godot and Endgame by Samuel Beckett are two of the most famous absurd plays of the 20th century. Some previous analyses have been dealing a great deal with the philosophy of the absurd and the socio-economic critique in the works. This article tries to give a new view examined from the standpoint of the psychology of the author and through the theory of psychoanalysis of Sigmund Freud. Concepts that are used are Freudian slips, as well as symbols and free associations. This article will explore the relationship between the author’s past with his works and the ways in which the author reflects his latent desires into his work. In can be concluded that there is a common thread between the events in the author's past, and that they contribute to the author’s psychological disorders that are expressed in the two works.Keywords: Freud, Beckett, thanatos, psychobiography